Terri Coutee: ASPS Patient of Courage, 2018 - Chrysopoulo, Minas T. (Plast Reconstr Surg Glob Open, 2019)
Mrs. Terri Coutee was selected as an American Society of Plastic Surgeons (ASPS) Patient of Courage in 2018. Following successful treatment of her second breast cancer, which included a double nipple-sparing mastectomy and delayed deep inferior epigastric perforator (DIEP) flap breast reconstruction, Terri changed her career path from teaching to patient advocacy. In 2016, she launched DiepCFoundation.org, a non-profit organization that provides education, support, resources, and a community for women and men seeking information about breast reconstruction after mastectomy. Today, DiepCFoundation connects patients and physicians on a global scale, fostering a shared decision-making approach to breast reconstruction.